2005
DOI: 10.1080/02786820500430357
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Electrical Charge on Diesel Particles

Abstract: Nanoparticles (D p < 50 nm), which are formed as diesel engine exhaust cools and dilutes, constitute minority of total particle mass but majority of total particle number. There are several different theories to explain the nucleation of nanoparticles from diesel exhaust. The two main theories are homogeneous binary nucleation of sulfuric acid and water, and ion-induced nucleation. This study examined the ion-induced nucleation theory. In order to test the ionic nucleation theory, the charged fraction of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Hence, the overload of the devices led to inaccurate measurements, characterized by a significant underestimation by the P-TRAK and a potential measurementerror in the miniDiSC. In theory, the charging efficiency of the miniDiSC could have been influenced by increased particle charge in proximity to exhaust pipes or due to specific fuel additives that increase charge of exhaust particles (Jung and Kittelson 2005). But neither the measurements during highway maintenance work nor the stationary measurements showed any indications of such an effect being of practical relevance.…”
Section: Discussionmentioning
confidence: 90%
“…Hence, the overload of the devices led to inaccurate measurements, characterized by a significant underestimation by the P-TRAK and a potential measurementerror in the miniDiSC. In theory, the charging efficiency of the miniDiSC could have been influenced by increased particle charge in proximity to exhaust pipes or due to specific fuel additives that increase charge of exhaust particles (Jung and Kittelson 2005). But neither the measurements during highway maintenance work nor the stationary measurements showed any indications of such an effect being of practical relevance.…”
Section: Discussionmentioning
confidence: 90%
“…9 The above-mentioned study by Farfaletti and colleagues 8 found that the Ce catalyst was inefficient in the heavy-duty engine for all emissions except for B[a]P-TEQ (38% reduction), but markedly reduced all emissions except NO x (unchanged) in the light-duty engine. Another study by Jung and colleagues, 5 focusing on the kinetics of oxidation and combustion chemistry, reported a substantial increase of ultrafine particles emitted from a diesel engine combusting a fuel doped with a different commercial CeO 2 -based additive Eolys DPX-9 (Rhodia Electronics & Catalysis, La Rochelle, France).…”
Section: Introductionmentioning
confidence: 99%
“…PM emitted from diesel engine is charged particle [2]. Charge induced type PM sensor we designed can measure by real-time and it doesn't need particle collection apparatus.…”
Section: Pm Sensor For Exhaust Systemmentioning
confidence: 99%